Striking out: Biases and losses of retail option traders - Aleksi Pitkäjärvi; Matteo Vacca (Tinbergen Institute, 2024)
Analyzing over 15 years of account-level trading records from Finland, we show that option features-expiration, moneyness, and the strike price-influence the behavior of retail investors and exacerbate their behavioral biases. Retail investors selectively exploit the expiration feature of options to mitigate the psychological costs associated with selling losing positions, generating a strong disposition effect especially for out-of-the-money options. They also use the strike price of an option as an objective, instrument-specific reference point when making their selling decisions. Behavioral biases contribute to heterogeneity in option trading performance, with the worst performance concentrated among investors with the strongest biases.
Keywords: G41; G40; G50; G11; 330; options; retail investors; behavioral biases; disposition effect